Oxidation Kinetics of Magnesium‐Manganese Oxides for High‐Temperature Thermochemical Energy Storage. Issue 10 (7th September 2020) - Randhir, Kelvin; King, Keith; Petrasch, Joerg; Klausner, James
Abstract : In this article, the high‐temperature (≥1000 °C) oxidation kinetics of porous magnesium‐manganese oxide structures considered for large‐scale thermochemical energy storage are determined. For this analysis, oxides with Mn/Mg molar ratios of 2/3, 1/1, and 2/1 are synthesized via solid‐state reaction and crushed to a powder with particle sizes ranging from 125 to 180 μm. The powder is thermally reduced at 1500 °C inside a heated alumina tube under argon flow. Subsequently, the resulting porous bed is oxidized at temperatures between 1000 and 1500 °C with an oxygen to argon molar ratio of 1:4 (leading to an oxygen partial pressure of 0.2 atm). An Arrhenius‐type kinetic rate law is derived using the theory of internal oxidation assuming spherical particles. Subsequently, the kinetic rate law parameters are identified by comparing measured oxygen flow at the reactor outlet to the oxygen output computed using a 1D plug flow reactor model incorporating the postulated kinetic model. Results indicate that the derived bulk kinetic rate law describes the measured oxidation kinetics well and is suited for designing thermochemical energy storage modules based on magnesium‐manganese oxides. Abstract : Herein, a kinetics model is developed to describe the oxidation kinetics of Mg‐Mn oxide. The model is derived on the basis of the theory of internal oxidation. The model will be useful in predicting the power output of a thermochemical energy storage systems made out of Mg‐Mn oxides as the reactive material.